KOHESI SOSIAL (SOCIAL COHESIVENESS) MASYARAKAT LOKAL (KAJIAN TENTANG DERIVASI MAKANAN BERBASIS BAHAN SAGU DI KABUPATEN KEPULAUAN MERANTI RIAU) - Regita Rahmadhani A; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted by researchers at the Sago Berkah production house, West Banglas Village, Tebing Tinggi District, Meranti Islands Regency, Riau with the aim of knowing the forms of social cohesion or cohesiveness in the relationship between workers and owners of the Sago Berkah production house and its relationship with other businesses around and to find out the derivatives of sago-based food in the Sago Berkah production house. This research uses descriptive qualitative methods with census sampling techniques carried out using observation, in-depth interviews and documentation (photos and recording devices) research methods. The reference in this research guide uses the theory of Social Cohesion from Emile Durkheim's figure listed in his thesis entitled